IMMUNOLOGICAL ASPECTS OF INFLAMMATORY DISEASES OF THE ORAL MUCOSA IN CHRONIC RENAL FAILURE - Sabirov Bobur Kadirbaevich; Khabibova Nazira Nasullaevna (Modern American Journals, 2025)
This study investigates the immunological mechanisms underlying inflammatory lesions of the oral mucosa in patients with chronic renal failure (CRF). The analysis is based on clinical and biochemical data obtained from 90 subjects, including individuals with CRF, patients with chronic kidney disease (CKD) without renal insufficiency, and healthy controls. Salivary lactoferrin was evaluated as a local immune parameter, with normalization against albumin concentration to account for reduced salivary flow in CRF. Despite elevated absolute levels of lactoferrin in the CRF group, the lactoferrin-to-albumin ratio was significantly decreased (p < 0.05), indicating a deficiency in mucosal immune function. Clinically, CRF patients demonstrated impaired wound healing, atrophic gingival morphology, and pronounced periodontal tissue destruction in the absence of classical hyperemic signs. The data confirm a disruption of local innate immunity associated with renal insufficiency, mediated by altered neutrophil-mucosal interactions and salivary protein imbalance. The findings support the use of the lactoferrin/albumin index as a diagnostic marker of mucosal immune suppression in CRF and highlight the necessity for immunologically guided dental management in nephrology patients.
Keywords: Chronic renal failure; oral mucosa; salivary lactoferrin; mucosal immunity; local immune dysfunction; inflammatory oral diseases; CKD; periodontal pathology; albumin-normalized biomarkers; oral immunodiagnostics.